Measurement of Glucose/Insulin Fasting Ratio (G:I Ratio) for Insulin Resistance Identification on Polycystic Ovary Syndrome Patients - Fidel G. Siregar (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To identify insulin resistance on PCOs patients and to know characteristics and clinical differences between PCOs patients with and without insulin resistance in Gynecologic Outpatient Clinic of H. Adam Malik Hospital, Clinic of Prof. Delfi Lutan, Clinic of Prof. Thamrin Tanjung and Clinic of Halim Fertility Center in Medan. Method: This descriptive cross sectional study conducted from July 2008 - June 2009, diagnosis of PCOs based on Rotterdam’s criteria was drawn for 5 ml blood samples, from mediana cubiti vein, after 10 - 12 hours fasting for determination of fasting glucose, fasting insulin, LH, FSH, prolactin and testosterone. Insulin resistance was determined by glucose/insulin fasting ratio < 4.5. Result: From sixty one patients were divided into PCOs without insulin resistance (50 patients; 82%) and PCOs with insulin resistance (11 patients; 18%) group. No significant differences in clinico-biochemical characteristics, fasting glucose mean level, menstrual pattern, ovary volume, follicle number and reproductive hormone profile of two groups, except in BMI value, fasting insulin level and G:I ratio (p < 0.05). Conclusion: There was significant correlation between fasting insulin level and insulin resistance with mean of fasting insulin level of 24.882 μU/ml. Insulin resistance was frequent on overweight group study according to WHO criteria (BMI 25 - 29.9 kg/m2). [Indones J Obstet Gynecol 2011; 35-2: 74-8] Keywords: insulin resistance, polycystic ovary syndrome, G:I ratio